International Alignment between Interests and Ideology: The Case of China's Partnership Diplomacy - Georg Strüver (German Institute of Global and Area Studies (GIGA), 2016)
This paper examines the determinants of alignment in bilateral partnerships. While it was impossible to think about international cooperation without referring to the term "alliances" during much of the Cold War period, strategic partnerships have taken a central place in many states' diplomatic toolkits over the past two decades. This paper sheds light on such international alignment decisions by examining the case of China's partnership diplomacy in the period from 1990 to 2014. Theoretically, the analysis draws on scholarly insights about alliance formation and international cooperation to formulate two broad assumptions about partner choice, which are based on interest-driven and ideology-based rationales of alignment. Binary regression estimations highlight the importance of economic interests in explaining partnership onset. In contrast to common arguments about alliance formation, partnerships seem to be less driven by shared domestic ideologies. In fact, bilateral partnerships help bridge ideological gaps, enabling the partners' pursuit of economic gains and diplomatic preferences, at least in the case of China.
Keywords: 300; China; foreign policy; international cooperation; strategic partnerships